(415) Lecture Notes on Regression Analysis (Part 1) ملاحظات حول محاضرة تحليل الانحدار (الجزء الأول) - J. Van Rees, C. (معهد التخطيط القومى, 2024)
This academic work examines the theoretical and methodological foundations of regression analysis as one of the most important statistical techniques used to investigate and interpret relationships among economic and social variables. The study aims to provide an instructional framework explaining the nature of regression models and their applications in economic analysis, with particular emphasis on model construction and the selection of appropriate mathematical forms. The paper begins by presenting the historical background of the concept of regression, referring to the contribution of Sir Francis Galton, who first introduced the term while studying relationships between characteristics of parents and their children. His work led to the development of the concept of “regression toward the mean.” The study then explains the importance of economic theory in identifying the variables that should be included in analytical models, emphasizing that model construction should not rely solely on statistical procedures but must also be guided by theoretical economic foundations. The research discusses the distinction between dependent and independent variables and explains their roles in interpreting economic relationships. It also presents several mathematical forms commonly used in empirical analysis, including linear models, double-logarithmic models, and selected nonlinear forms, while explaining the mathematical and economic characteristics of each specification. Furthermore, the study addresses methodological issues related to model selection and argues that uncertainty concerning the true functional relationship between variables represents one of the central challenges in econometric analysis. It also notes that changes in economic behavior over time may reduce the reliability of models estimated from historical data when they are used for forecasting future developments. The work additionally provides practical applications involving household expenditure patterns and Engel curves, explaining concepts of economic elasticity and the classification of goods according to consumer responses to income changes. The academic value of the study lies in its provision of a fundamental introduction to econometric analysis and its practical applications in economic planning and policy-making.